2018
DOI: 10.1021/acs.est.8b01913
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production and Conductive Materials: A Critical Review

Abstract: Conductive materials (CM) have been extensively reported to enhance methane production in anaerobic digestion processes. The occurrence of direct interspecies electron transfer (DIET) in microbial communities, as an alternative or complementary to indirect electron transfer (via hydrogen or formate), is the main explanation given to justify the improvement of methane production. Not disregarding that DIET can be promoted in the presence of certain CM, it surely does not explain all the reported observations. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
133
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 320 publications
(137 citation statements)
references
References 148 publications
2
133
0
2
Order By: Relevance
“…Recently, there has been a great interest in applying conductive materials for enhancing CH 4 production in anaerobic digestion processes (for a recent overview, see Martins et al). These materials, which include GAC, carbon cloth and biochar, among others, can stimulate DIET yielding improved CH 4 production rates .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, there has been a great interest in applying conductive materials for enhancing CH 4 production in anaerobic digestion processes (for a recent overview, see Martins et al). These materials, which include GAC, carbon cloth and biochar, among others, can stimulate DIET yielding improved CH 4 production rates .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is very important to note that as hydrogen is produced by fermentative bacteria and utilized by hydrogenotrophic methanogens, this coupling requires an interspecies electron transfer (IET) process . In fact, recent works have reported that supplementing anaerobic consortia with conductive materials promotes IET enhancing CH 4 production . The electron transfer among microorganisms without mediating diffusive electron carriers is known as direct interspecies electron transport (DIET) and, according to the literature, there are two types of DIET mechanisms: via conductive pili with cytochromes involved, and via abiotic transfer with external conductive materials .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations